An efficient front‐tracking method for simulation of multi‐density bubbles. (21st December 2016) - Mehrabani, M. T.; Nobari, M. R. H.; Tryggvason, G.
Abstract: In this article, a masked bubble strategy is proposed using the front‐tracking method when simulation of multi‐density bubbles to reduce remarkably the computational cost from both the RAM usage and the number of computations at each time step comparing with the regular method. In the masked bubble strategy, instead of using full domain to update the properties at each time step, each bubble is considered as enclosed in the smallest box required to compute the properties based on the Peskin's function, which needs at least two full mesh sizes from both sides of the interface of each bubble in any directions. To show the performance of the masked bubble strategy in the front‐tracking method, we study the multi‐density bubbles motion in a curved duct flow induced by a pressure gradient in the absence of gravity. To solve the density Poisson equation, the parallel direct solver scheme is tested. The comparison of numerical simulations at the same conditions indicates that the parallel direct solver scheme under the masked bubble strategy considerably reduces the computational time and RAM usage relative to the regular full‐domain method, providing using simulations on finer grid resolutions. Copyright © 2016 John Wiley & Sons, Ltd. Abstract : Schematic comparison of the masked bubble strategy versus full‐domain strategy in front‐tracking method in a curved duct.